1983
DOI: 10.1002/hlca.19830660208
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Benzo[c]phenanthridine Alkaloids Sanguinarine, Chelirubine and Macarpine

Abstract: SummaryThe biosynthesis of the benzo [clphenanthridine alkaloids was investigated in a cell suspension culture of Macleaya cordata (papaveraceae). Feeding experiments define the biosynthetic pathway (-)-7,8,13,13 a-tetrahydrocoptisine -+ (-)-cis-Nmethyl-7,8,13,13a-tetrahydrocoptisinium salt 15 + protopine (5) -+ sanguinarine (1) -+ chelirubine (3)+ macarpine (4).Sanguinarine (1) and chelerythrine (2) belong to the benzo [clphenanthridine alkaloids class [I]. These alkaloids occur widely in papaveraceous plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…We report here on a biosynthetic investigation of corycavinium (lc) as a key intermediate in the route from protoberberine-type to hexahydrobenzo-[c]phenanthridine-type alkaloids, an investigation using the callus tissues of Corydalis incisa (Papaveraceae). The callus tissues of C. incisa were derived from the stem tissue, and in the suspension cultures the substrates, 13 C-labelled (±)-7V r -methyl-w^ö-tetrahydrocorysaminium (4) chloride and (±)-corycavinium (lc) chloride, were administered according to the previously described procedure [3]. In Table 7, the results of the feeding experiments are listed.…”
Section: Fig 1 Molecular Structure Of (-J-corycavinium ( + )-10-cammentioning
confidence: 99%
See 1 more Smart Citation
“…We report here on a biosynthetic investigation of corycavinium (lc) as a key intermediate in the route from protoberberine-type to hexahydrobenzo-[c]phenanthridine-type alkaloids, an investigation using the callus tissues of Corydalis incisa (Papaveraceae). The callus tissues of C. incisa were derived from the stem tissue, and in the suspension cultures the substrates, 13 C-labelled (±)-7V r -methyl-w^ö-tetrahydrocorysaminium (4) chloride and (±)-corycavinium (lc) chloride, were administered according to the previously described procedure [3]. In Table 7, the results of the feeding experiments are listed.…”
Section: Fig 1 Molecular Structure Of (-J-corycavinium ( + )-10-cammentioning
confidence: 99%
“…-Since 1867, there have been chemical studies [1] of protopine-type alkaloids, produced by all papaveraceae spp., with contemporary efforts focussed on this group's biosynthetical behavior [2][3][4][5]. Protopine-type alkaloids function as key intermediates in the metabolism of the protoberberine type (Scheme 1).…”
mentioning
confidence: 99%
“…Benzo[c]phenanthridine alkaloids have been biosynthesized from the corresponding protoberberine alkaloids presumably via a 3-arylisoquinoline intermediate. 6) Cerasonine 1, 7) a phenolic protoberberine, was isolated from Polyalthia cerasoides (ROXB.) BEDD.…”
mentioning
confidence: 99%
“…[17][18][19][20] The synthetic strategy involved in the coupling reaction of Nmethyl-o-toluamide with benzonitrile derivatives. 21 Retrosynthetic analysis of both alkaloids suggested that the coupling reaction of o-toluamide 1 with benzonitrile 2 affords 3-arylisoquinoline 3, which could be converted to 8-oxoberberine 4 via S N 2 type cyclization of amide nitrogen.…”
mentioning
confidence: 99%